From a View of the Hospital as a System to a View of the Suffering Patient - Gillie Gabay; Smadar Ben-Asher (Frontiers Media S.A., 2022)
Purpose: Hospitals aspire to provide patient-centered care but are far from achieving it. This qualitative mixed methods study explored the capacity of hospital directors to shift from a hospital systemic-view to a suffering patient-view applying the Salutogenic theory.Methods: Following IRB, we conducted in-depth narrative interviews with six directors of the six Israeli academic tertiary public hospitals, focusing on their managerial role. In a second meeting we conducted vignette interviews in which we presented each director with a narrative of a suffering young patient who died at 33 due to medical misconduct, allowing self-introspection. Provisional coding was performed for data analysis to identify categories and themes by the three dimensions of the sense-of-coherence, an anchor of Salutogenics: comprehensibility, manageability, and meaningfulness.Results: While at the system level, directors reported high comprehensibility and manageability in coping with complexity, at the patient level, when confronted with the vignette, directors acknowledged their poor comprehensibility of patients' needs and patient's experience during hospitalizations. They acknowledged their poor capacity to provide patient-centered care. Meaningfulness in the narrative interview focused on the system while meaningfulness in the vignette interview focused on providing patient care.Conclusions: The evident gaps between the system level and the patient level create lack of coherence, hindering the ability to cope with complexity, and are barriers to providing patient-centered care. To improve the delivery of patient-centered care, we suggest ways to consolidate the views, enabling the shift from a systemic-view to a patient-view.